Discogobio acutusirostris, a new species of cyprinids (Teleostei: Cypriniformes) from the middle Chang-Jiang basin in Guizhou Province, China - Deng, Shu-Qing; Deng, Chao; Zhang, E. (Zootaxa, 2026)
Discogobio acutusirostris, a new species, is here described from the Yuanjiang River of the middle Chang-Jiang basin in Guizhou Province, Southwest China. It can be assigned to the species group of Discogobio diagnosed by having a large mental adhesive disc with its edge margin extending to or beyond the vertical through the anterior edge of eye and a snout covered with small tubercles. The new species is separated from all other species of this group by having many rows of dark brown spots along scale rows on the flank, an unscaled region of the abdomen adjacent to the ventral mid-line restricted only to the bases of pectoral fins, a shorter snout, a stout caudal peduncle and shorter pectoral fins. The validity of D. acutusirostris is also corroborated in a phylogenetic analysis based on the cytochrome b gene. A lectotype is here designated for D. brachyphysallidos.